2013
DOI: 10.1021/bi400554s
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation between the Two Heads of Smooth Muscle Myosin Is Essential for Full Activation of the Motor Function by Phosphorylation

Abstract: The motor function of smooth muscle myosin (SmM) is regulated by phosphorylation of the regulatory light chain (RLC) bound to the neck region of the SmM heavy chain. It is generally accepted that unphosphorylated RLC induces interactions between the two heads and between the head and the tail, thus inhibiting the motor activity of SmM, whereas phosphorylation of RLC interrupts those interactions, thus reversing the inhibition and restoring the motor activity to the maximal value. One assumption of this model i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 27 publications
0
20
1
Order By: Relevance
“…These data suggest ADP release is rate-limiting, so acto·M10HMM·ADP will be the predominant steady-state intermediate, making this a high duty ratio motor. Regarding the difference between the current results with HMM and the earlier results with subfragment-1 (S1), it is worth noting that a recent paper has produced evidence of smooth muscle myosin-2 S1 has a much lower steady-state actinactivated ATPase activity than HMM (67).…”
Section: Discussioncontrasting
confidence: 96%
“…These data suggest ADP release is rate-limiting, so acto·M10HMM·ADP will be the predominant steady-state intermediate, making this a high duty ratio motor. Regarding the difference between the current results with HMM and the earlier results with subfragment-1 (S1), it is worth noting that a recent paper has produced evidence of smooth muscle myosin-2 S1 has a much lower steady-state actinactivated ATPase activity than HMM (67).…”
Section: Discussioncontrasting
confidence: 96%
“…We found that both RLC12b and RLC9 in Myo19 can be phosphorylated by MLCK, but this phosphorylation has little effect on the motor activity of Myo19-truncated constructs. It is known that phosphorylation of RLC by MLCK regulates the motor activity of smooth muscle myosin but not the truncated smooth muscle myosin having the coiled-coil tail completely deleted (22). Thus, it is possible that MLCK regulates the motor activity of full-length Myo19, but not the truncated Myo19.…”
Section: Discussionmentioning
confidence: 99%
“…Oligonucleotides were synthesized by Invitrogen. Actin, CaM, and MLCK (myosin light chain kinase) were prepared as described previously (22,23). Two mouse myosin-5a constructs, i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myosin-5a HMM, rabbit skeletal muscle, and actin were prepared as described previously. 14 , 27 , 28 …”
Section: Methodsmentioning
confidence: 99%